The perils of peace : the public health crisis in occupied Germany - Reinisch, Jessica (Oxford : Oxford University Press, 2013)
This is an archive-based study examining how the four Allies - Britain, France, the United States and the Soviet Union - prepared for and conducted their occupation of Germany after its defeat in 1945. It uses the case of public health to shed light on the complexities of the immediate post-war period.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on June 26, 2013).
Keywords: Public health -- Germany -- History -- 20th century; Public health administration -- Germany -- History -- 20th century; Germany -- History -- 1945-1955.; Germany -- Social conditions -- 1945-1955.